2005
DOI: 10.1667/rr3453.1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Damage after Fractionated Whole-Brain Irradiation in Rats

Abstract: Whole-brain irradiation of animals and humans has been reported to lead to late delayed structural (vascular damage, demyelination, white matter necrosis) and functional (cognitive impairment) alterations. However, most of the experimental data on late delayed radiation-induced brain injury have been generated with large single doses or short fractionation schemes that may provide a less accurate indication of the events that occur after clinical whole-brain radiotherapy. The pilot study reported here investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 39 publications
5
87
0
Order By: Relevance
“…155,157 Vascular density in cerebral tissue decreases over time. 158 The large vessels in the central nervous system have large muscular tunica media and are more resistant to radiation; however, the structural integrity of the endothelium in these larger vessels is also reduced over time. 159 Ultimately, histopathological changes similar to those of advanced atherosclerosis occur and result in luminal narrowing and thrombus formation.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…155,157 Vascular density in cerebral tissue decreases over time. 158 The large vessels in the central nervous system have large muscular tunica media and are more resistant to radiation; however, the structural integrity of the endothelium in these larger vessels is also reduced over time. 159 Ultimately, histopathological changes similar to those of advanced atherosclerosis occur and result in luminal narrowing and thrombus formation.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…162 Preexisting atherosclerosis at time of treatment may be an exacerbating factor. 158,163 Consequently, risk factors include hypertension, obesity, smoking, diabetes mellitus, and other known associations with both cardiac and cerebrovascular disease in the general population.…”
Section: Carotid Artery Diseasementioning
confidence: 99%
“…Rosner studied 100 breast cancer patients with symptomatic BM which treated with multifarious chemotherapies, its brain‐specific objective response rate surprisingly rises to 50% 31. Meanwhile, radiation is also known to disrupt the BBB,32 but finally this way could not achieve good prognosis. At this point, the combined therapy was taken into consideration.…”
Section: The Bbb Penetration and Bmmentioning
confidence: 99%
“…Moreover, two animal studies (30,31) have demonstrated that the intake of ACEIs have reduced the prevalence of radiation induced brain injuries, including cognitive impairment and optic neuropathy. Other studies have explored the association between ACEIs and gastrointestinal (GI) toxicity.…”
mentioning
confidence: 99%